2004
DOI: 10.1093/bja/aeh237
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe postpartum haemorrhage by uterine artery embolization

Abstract: We report a case of postpartum haemorrhage which was successfully treated by embolization of the uterine artery. This technique is not well known and is thought to be underused in this condition. We wish to alert medical personnel to its role in this life-threatening situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…23 The internal iliac arteries may be catheterised prophylactically under local anaesthesia 18 and the catheter used either for temporary balloon inflation or more permanent embolisation. [14][15][16][17][18] The advantage of prophylactic catheterisation is that rapid endovascular occlusion may be achieved with balloon tamponade in the event of massive haemorrhage. One potential benefit of this technique is that non-specialist staff, including anaesthetists with suitable training, could initiate balloon occlusion in the presence of uncontrollable haemorrhage whilst specialist radiological advice is sought.…”
Section: Discussionmentioning
confidence: 99%
“…23 The internal iliac arteries may be catheterised prophylactically under local anaesthesia 18 and the catheter used either for temporary balloon inflation or more permanent embolisation. [14][15][16][17][18] The advantage of prophylactic catheterisation is that rapid endovascular occlusion may be achieved with balloon tamponade in the event of massive haemorrhage. One potential benefit of this technique is that non-specialist staff, including anaesthetists with suitable training, could initiate balloon occlusion in the presence of uncontrollable haemorrhage whilst specialist radiological advice is sought.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter arterial embolization has been a recognized method of controlling hemorrhage since the 1960s, and has been used to control pelvic bleeding secondary to malignancy, trauma, and postradiation. 7 Several agents for embolization like gelatin sponge pledgets, polyvinyl alcohol particles, and steel coils are currently in use. Brown et al 8 reported the first case of selective arterial embolization to successfully treat extrauterine pelvic hematoma to control bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Indikationen für die Embolisation der Aa. uterinae sind die atone Nachblutung, aber auch umschriebene uterine oder pelvine Blutungen [16]. Die Embolisation wurde bei unserer Patientin vom interventionellen Radiologen im OP mittels C-Bogen durchgeführt, sollte aber aufgrund der besseren Untersuchungsbedingungen bei hämodynamisch stabilen Patientinnen an einem Angiografie-Arbeitsplatz vorgenommen werden [17].…”
Section: Maßnahmen Im Beschriebenen Fallunclassified